Kualitas Pelayanan terhadap Kepuasan Masyarakat - Kharisma Oktora; Evi Mayang Sari; Tiris Sudrartono (Journal of Management and Bussines (JOMB), 2023)
The purpose of this study was to determine community satisfaction in making new KTPs in Paseh District, Bandung Regency. The method used in this study is descriptive qualitative, the data sources used are primary data sources and secondary data sources related to empirical situations and conditions of community satisfaction in the service of making KTPs in the sub-districts. The results showed that the t test value showed t count > t table, namely 8.028 > 2.042. In conclusion, community satisfaction with the service for making KTPs in Paseh District, Bandung Regency can be seen from the simplicity of the waiter procedure, Paseh District, Bandung Regency, the procedure for making KTPs is simple and straightforward. The time of service, Paseh District, Bandung Regency in completing the making of KTP was in accordance with SOP (standard operating procedure). Keywords: Community Satisfaction, KTP, Servant